Literature Study: Application of Positive Psychology to the Field of Education in Indonesia - Ramadhanti, Auliya (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: This study aims to determine the application of positive psychology, especially in the field of education in Indonesia, which has a large impact on students and teachersMethodology: This research is a literature study using descriptive qualitative research methods through literature studies that examines Positive Education implemented in the Merdeka Belajar curriculum and its psychological benefits for students.Main Findings: Positive education is an attractive solution to improve the welfare and happiness of students in learning at school, in line with Merdeka Belajar which is the Government's weapon as an effort to improve the quality of students. students are also the main goal.Novelty/Originality of this study: Based on the literature study conducted on positive education, it can be concluded that positive education has become a view that is widely recommended for the education system, but in practice it is still not implemented even though there is an Independent Learning curriculum, successful implementation with the collaboration of the academic community and students will help Indonesia improve the quality of students.